Quality Analysis Reviewed from Organoleptic Properties, Water Content and Reducing Sugar Content of Pure Honey (Apis dorsata) and Mixed Honey - Musparlin Halid; Wulan Ratia Ratulangi (Universitas Nahdlatul Ulama Surabaya, 2023)
Determination of honey quality standards in principle aims to protect consumers from honey products that do not meet the requirements and protect good honey products from counterfeiting. The purpose of this study was to analyze differences in quality in terms of organoleptic properties, water content, and reducing sugar content in pure honey and mixed honey. This research uses a true experimental design conducted at the Chemistry Laboratory of the Health Polytechnic of Mataram, while the sampling was carried out in Lantung, Sumbawa Besar, Indonesia. The research was conducted from January to May 2022. Samples were taken purposively based on the characteristics of each honey. Data analysis used independent T-Test with 95% confidence level (p = 0.05). Based on the results of organoleptic tests that there are differences between the color, taste, and viscosity of pure honey and mixed honey. Furthermore, the water content in pure honey with an average of 19.01% and 20.83% in mixed honey, this indicates that when mixing honey uses a lot of water as a mixture. Based on the results of the Independent Sample T-Test, it was seen that there was a difference between the water content and reduced sugar content in both pure honey and mixed honey with a P-value = 0.00 < 0.05, meaning that there was a significant difference. Thus, the organoleptic quality of pure honey, water content, and reduced sugar is much better and has met the standard for honey that is suitable for consumption compared to mixed honey.